The Challenges of Girl-Child Education in Ungogo Local Government Area of Kano State in Nigeria on 1999-2019 - Nasidi, Nadir A.; Wali, Rukayya Maisara (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Since the introduction of Western education to Northern Nigeria, especially in the 1920s, many Muslims in the region found it objectionable as it tempered with their religio-cultural values including for instance, co-education. In light of this therefore, this paper identifies and examines the major challenges affecting girl child education in Ungogo Local Government Area of Kano State, Nigeria. Using both primary and secondary sources that are augmented with a qualitative data analysis, the researchers administered a total number of 120 questionnaires across five (5) political wards of Ungogo Local Government Area that were purposively sampled. Out of the 120 questionnaires administered, only 105 were retrieved representing 87.5% response rate. Data collected is analysed using descriptive statistics. Results revealed that religio-cultural reasons, poverty, lack of viable government educational policies and parental preference to educate the male child are the major factors curtailing the chances of the girl child to have access to western education in the area of study.